Bhutan : Technical Assistance Evaluation Report (March 4-8, 2013). (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Bhutan's Technical Assistance Evaluation report. Participation in the statistical projects financed by the Japanese government in national accounts, prices, government finance, and balance-of-payments statistics is having a major effect on Bhutan's statistical development. The statistical compilers were well informed about the donor as the source of funding. The method of combining regional workshops and multiple missions was considered to be particularly suitable. Cross-sectoral data consistency and coordination are increasingly recognized as important. Computerized accounting systems for the budgetary central government have been introduced, namely the Multi-Year Rolling Budget and the Public Expenditure Management System.